Random laser action from a natural flexible biomembrane-based device. Issue 13 (19th July 2016) - Liu, Xiyun; Li, Tingshuai; Yi, Tao; Wang, Chuanke; Li, Jin; Xu, Min; Huang, Dengfeng; Liu, Shenye; Jiang, Shaoen; Ding, Yongkun
Abstract: Incoherent random lasing action in flexible eggshell membranes infiltrated with rhodamine 6G laser dyes is demonstrated. Laser radiation is achieved by exciting samples with 1-ns pulses at 526 nm. A threshold of 58 μJ/pulse is measured for the samples. The minimum threshold decreases to 35 μJ/pulse after the sample is coated with gold nanoparticles using a magnetron sputtering technique. The peaks of emission spectra are observed to redshift from 576 to 596 nm as dye concentration rises from 0.03 to 0.6 wt%. A linewidth of approximately 5 nm is obtained for most samples. This study is expected to offer a new way to induce lasing emission using biological microfibrils, and enriches basic knowledge of biophotonics.